Teaching Toxicology With Simulation: A Model Curriculum for Emergency Medicine - Nicholas Nacca; Urvi Mevar; Jeanna Marraffa (Association of American Medical Colleges, 2014)
Abstract This simulation toxicology curriculum consists of 8-1 hour simulation sessions with effort to teach diagnosis and management of toxicological emergencies to Emergency Medicine Residents in their second year of training. We review the toxicological emergencies as outlined by the 2009 Model of the Clinical Practice of Emergency Medicine, and list those topics directly addressed by the curriculum, and those that require alternative instructional methods. This project represents the culmination and organization of our medical and clinical toxicologists educational curriculum which has been developed through years of experience.